2017
DOI: 10.1103/physreva.95.053863
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of stable dark- and bright-soliton Kerr combs in normal-dispersion resonators

Abstract: Using the Lugiato-Lefever model, we analyze the effects of third-order chromatic dispersion on the existence and stability of dark-and bright-soliton Kerr frequency combs in the normal dispersion regime. While in the absence of third-order dispersion only dark solitons exist over an extended parameter range, we find that third-order dispersion allows for stable dark and bright solitons to coexist. Reversibility is broken and the shape of the switching waves connecting the top and bottom homogeneous solutions i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 53 publications
(78 reference statements)
10
56
1
Order By: Relevance
“…This term breaks the reflection symmetry x → −x, inducing the drift of the LSs and the modification of the collapsed snaking as reported in Ref. [70]. Although these effects are very relevant regarding real physical systems, their study is beyond the scope of the present work and will be examined elsewhere.…”
Section: Bifurcation Structure Of Type-i Localized Statesmentioning
confidence: 67%
See 1 more Smart Citation
“…This term breaks the reflection symmetry x → −x, inducing the drift of the LSs and the modification of the collapsed snaking as reported in Ref. [70]. Although these effects are very relevant regarding real physical systems, their study is beyond the scope of the present work and will be examined elsewhere.…”
Section: Bifurcation Structure Of Type-i Localized Statesmentioning
confidence: 67%
“…A natural extension of this work must include the effect of the temporal walk-off, which breaks the x → −x symmetry inducing asymmetry and drift. We expect that for weak walkoff the collapsed snaking is modified in the same fashion as in the context of Kerr cavities in the presence of third-order dispersion [70].…”
Section: Discussionmentioning
confidence: 92%
“…In (124), it was demonstrated that the dynamics of platicons in the presence of the third-order dispersion is quite peculiar and drastically different from bright solitons. In (125), a possibility of stable coexistence of dark and bright solitons in case of nonzero third-order dispersion was revealed.…”
Section: Normal Dispersion Solitonic Pulsesmentioning
confidence: 99%
“…92,93 Although the original nonlinear Schrödinger equation admits a solution in the form of bright solitons in the anomalous-dispersion regime, dark solitons are in the normal-dispersion regime. 94,95 It is worth noting that mode-locking transitions do not necessarily correspond to dark or bright pulse (soliton) generation in microresontors with normal dispersion. 96,97 This is in contrast to the situations for the negative-dispersion regime where all soliton forms are actually "bright solitons."…”
Section: Dark Soliton Generation In the Normal-dispersion Regimementioning
confidence: 99%
“…95 In other words, it can be considered that there does not exist a rigid "barrier" to distinguish the two states (depending on the pulse duration and duty cycle). Since rich phenomena have been discovered exhibiting distinct features from different aspects and with rather complicated excitation dynamics, there have been various prediction and explanations related to the physical origin of the observed temporal behaviors for microcombs with normal dispersion in the literature, such as "platicons" (flat-topped bright solitonic pulses), 99 dark pulses, 23,92 and dark solitons 93,95,96 or just normal-dispersion microcombs. 97 In this part, we mainly focus on the mode-locked character, rather than a strict physical clarification for this kind of pulse.…”
Section: Dark Soliton Generation In the Normal-dispersion Regimementioning
confidence: 99%